Administrative Strategies of the Phrapariyattidhamma School’s General Education According to The Principle of Total Quality Management - ปภสฺสโร, พระสมุห์จักรกฤษ; Kunarak, Pragob (Journal of Dhamma for Life, 2025)
The objectives of this study were to: 1) examine current and desirable states of school administration, 2) prioritize needs for school administration, and 3) formulate school administrative strategies according to the concept to total quality management. Employing the mixed - method research design, the sample,random sampling technique was used to identify the studied sample, covering 201 Phiapariyattidhamma School’s General Education. A set of opinionnaire it was employed to collect data during March-August, 2024. All data were then analyzed by descriptive statistics: percentage, mean, standard deviation, PNI, and content analysis. The results revealed that: 1) Current state of school administration was at a moderate degree, where the desirable one was high. 2)The priority of administrative needs was budgeting, personnel, general, and academic functions respectively. 3) School administrative strategies were fourfold: 1) improvable school administrative system with emphasis on student’s needs.2) Creating social network for stakeholder participation. 3)Transitioning budget management towards digital budget system for school development. 4) improvable the measurement and evaluation system with authentic and diverse practices.